“LA NO DISCRIMINACIÓN EN EL CÓDIGO CIVIL ECUATORIANO EN CUANTO A LA IGUALDAD DENTRO DE LA INSTITUCIÓN DEL MATRIMONIO” - Pineda Tandazo, Jean Paul (2020)
This research constitutes in the final report of the investigation process motivated in the Constitution of the Republic of Ecuador in its article 11 numeral 2 which contemplates in its pertinent part that all people are equal and will enjoy the same rights, duties, and opportunities, that is to say, that all people are equal before the law, in this way no one can be discriminated against on the grounds of ethnicity, place of birth, age, sex, gender identity, sexual orientation, etc. However, this is violated in terms of the institution of marriage contemplated in article 81 of the Ecuadorian Civil Code where it establishes that marriage is a solemn contract between a man and a woman, limiting the union of people of the same sex or different sexual orientation since they cannot fulfill the aims of marriage. Which are: living together, helping each other and procreate; but, it is not considered that today there are marriages without children, in which they do not live together and in those that there is no mutual help. In this sense, it may well regulate the marriage of people of the same sex or different sexual orientation so that non-discrimination is effective and that they are not standardized differently. Furthermore, the present investigation contains conceptual references and doctrinal elements that allow the understanding of the legal problem and as a result of this investigative process, I could formulate the Civil Code as a legal proposal within the institution of marriage where it is modified and established that it is a solemn contract by which two people join, regardless of sex or sexual orientation, or limit the fulfillment of the purposes of marriage, allowing the procreation to be regulated in an assisted manner.